Is reading ability related to activation dumping speed? Evidence from immediate repetition priming. - Meiran, Nachshon (Memory & Cognition, 1996)
In parallel processing models, residual activity constitutes noise that must be dumped, and fast dumping is associated with efficient processing. Subjects performed a continuous lexical decision task with repetitions (Experiments 1 and 2). Efficient readers (who had high comprehension and vocabulary scores) showed smaller repetition priming than did inefficient readers, but mostly at Lag 0 (equivalent to 3-sec stimulus onset asynchrony SOA). Experiment 3 manipulated the empty interrepetition interval. It was found that reading ability was negatively related to repetition priming mostly when the SOA was 3 sec, but less so when it was 2 or 4 sec. Experiment 4 failed to find similar reading ability differences when the task was continuous recognition. The findings are interpreted as showing that efficient readers managed to dump residual activity related to subsemantic information in less than 3 sec, whereas inefficient readers required 3–4 sec. Reprinted by permission of the publisher.